Persistent Hypoglossal Artery as a Potential Risk Factor for Simultaneous Carotid and Vertebrobasilar Infarcts - Jin, Xingyi; Sun, Libo; Feng, Zheng; Li, Xiaodong; Zhang, Hongyan; Meng, Ke; Yu, Weidong; Fu, Chao (Frontiers in Neurology, 2018)
Persistent hypoglossal artery (PHA), a rare embryological carotid–basilar anastomosis, is usually accompanied by hypoplastic vertebral and posterior communicating arteries, and thereby such vascular anomaly serves as the main feeder supplying the vertebrobasilar territory. Although rarely reported, simultaneous anterior and posterior territory infarcts related to PHA and carotid atherosclerosis can occur. To date, as far as we know, only 3 such cases have been previously reported in the literature. Here, we present the case of a 65-year-old female with a PHA and carotid atherosclerotic plaques, who developed acute multiterritorial infarcts involving the left carotid and vertebrobasilar territories. This study highlights that such a persistent anastomosis should be considered when multiple infarcts involving the anterior and posterior territory are encountered, and should be kept in mind when dealing with carotid atherosclerotic lesion.